2007
DOI: 10.1007/s12013-007-0007-8
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical, pharmacological, and functional characteristics of cloned and native mammalian two-pore domain K+ channels

Abstract: The mammalian family of two-pore domain K+ (K2P) channel proteins are encoded by 15 KCNK genes and subdivided into six subfamilies on the basis of sequence similarities: TWIK, TREK, TASK, TALK, THIK, and TRESK. K2P channels are expressed in cells throughout the body and have been implicated in diverse cellular functions including maintenance of the resting potential and regulation of excitability, sensory transduction, ion transport, and cell volume regulation, as well as metabolic regulation and apoptosis. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
185
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(199 citation statements)
references
References 210 publications
(1,029 reference statements)
8
185
0
5
Order By: Relevance
“…The inward current induced by fluoxetine may be attributable to the inhibition of the low K2P basal activity, but also to the inhibition of delayed rectifier channels, that could be not completely blocked by our blockers solution, as previously reported (Hahn et al, 1999;Yeung et al, 1999). In general, quinine and quinidine are considered as K2P blockers (Lotshaw, 2007;Mathie and Veale, 2007), and in mSCG neurons, quinine (300 M) induced an inward current at Ϫ30 mV (Ϫ77.5 Ϯ 10.6 pA; n ϭ 8) that we attributed to the reduction of remaining M-current incompletely blocked by the blockers solution. Indeed, M-current inhibition by quinine has been reported in bullfrog sympathetic neurons (Imai et al, 1999) as well as in neuroblastoma cells (Robbins et al, 1992).…”
Section: Trek Channel Modulatorsmentioning
confidence: 48%
See 2 more Smart Citations
“…The inward current induced by fluoxetine may be attributable to the inhibition of the low K2P basal activity, but also to the inhibition of delayed rectifier channels, that could be not completely blocked by our blockers solution, as previously reported (Hahn et al, 1999;Yeung et al, 1999). In general, quinine and quinidine are considered as K2P blockers (Lotshaw, 2007;Mathie and Veale, 2007), and in mSCG neurons, quinine (300 M) induced an inward current at Ϫ30 mV (Ϫ77.5 Ϯ 10.6 pA; n ϭ 8) that we attributed to the reduction of remaining M-current incompletely blocked by the blockers solution. Indeed, M-current inhibition by quinine has been reported in bullfrog sympathetic neurons (Imai et al, 1999) as well as in neuroblastoma cells (Robbins et al, 1992).…”
Section: Trek Channel Modulatorsmentioning
confidence: 48%
“…There are no completely specific or selective modulators distinguishing among the different K2P channel subtypes (for review, see Lotshaw, 2007), and therefore, we tested several of the innumerable pharmacological agents that interact with them. While some enabled us to rule out the participation of a given subfamily or subtype with a degree of confidence, others strongly indicated that the TREK subfamily was the origin of the riluzoleactivated outward current.…”
Section: Trek Channel Modulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-pore domain K ϩ channels (K2P) 2 comprise the newest subfamily of K ϩ channels. Unlike other K ϩ channels that are tetramers, K2P channels are dimers with each subunit containing four transmembrane segments and two pore-forming loops (P-loop) (see Fig.…”
mentioning
confidence: 99%
“…L'influence des canaux K + sur l'excitabilité membranaire est primordiale et vient du fait que la modulation de nombre d'entre eux et une boucle P (Figure 3), à l'origine notamment des courants K + dits à rectification entrante, ses principaux représentants étant les canaux Kir et le canal bactérien KcsA ; enfin, (3) celle des sousunités de canaux à quatre DTM (M1-M4) et deux boucles P (Figure 3) appelés canaux 2P, générant des courants qui remplissent la plupart des critères de définition d'un courant de fond ou de fuite. Les canaux 2P s'assemblent en dimères et non en tétramères pour former les canaux TWIK, THIK, TREK, TASK, TALK et TRESK [9,10].…”
Section: Les Canaux Potassiquesunclassified